2020
DOI: 10.3390/ma13071660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylenediphenyl 4,4’-Diisocyanate and Maleic Anhydride as Coupling Agents on the Properties of Polylactic Acid/Polybutylene Succinate/Wood Flour Biocomposites by Reactive Extrusion

Abstract: Polylactic acid (PLA)/polybutylene succinate (PBS)/wood flour (WF) biocomposites were fabricated by in situ reactive extrusion with coupling agents. Methylenediphenyl 4,4’-diisocyanate (MDI) and maleic anhydride (MA) were used as coupling agents. To evaluate the effects of MDI and MA, various properties (i.e., interfacial adhesion, mechanical, thermal, and viscoelastic properties) were investigated. PLA/PBS/WF biocomposites without coupling agents revealed poor interfacial adhesion leading to deteriorated prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…MAPE was also selected as it is one of the most widely used additives, e.g. coupling agent, for increasing the compatibility, adhesion between cellulose bers and a thermoplastic matrix (Seo et al 2020). The coupling reaction between the cellulose ber and the MAPE is exposed in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…MAPE was also selected as it is one of the most widely used additives, e.g. coupling agent, for increasing the compatibility, adhesion between cellulose bers and a thermoplastic matrix (Seo et al 2020). The coupling reaction between the cellulose ber and the MAPE is exposed in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…The strength enhancement was due to the chemical reaction between coupling agents and raw materials, which decreased the content of hydrophilic hydroxyl groups on the wood surface, due to the grafting reaction with the silane of KH550, generating Si-O-C bonds [ 22 ]. Urethane bonds were formed by the reaction between the isocyanate groups of MDI and the hydroxyl groups of wood and plastics [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the A171-treated samples had a higher bonding strength than KH550-treated samples. Previous studies have demonstrated that methylenediphenyl-4,4′-diisocyanate (MDI) as a WPC coupling agent enhanced the mechanical properties due to the formation of stable urethane bonds between the isocyanate groups of MDI and the hydroxyl groups of wood [ 23 , 24 ]. Maleic anhydride is also an effective coupling agent for WPCs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 One of the most widely used modifications, due to its ease, is the use of coupling agents as a way of improving matrix-fiber adherence. [14][15][16] For example, the incorporation of coupling agents of methylene 4,4 0 diphenyl diisocyanate and maleic anhydride in the polylactic acid/ polybutylene succinate/wood flour matrix, to improve the mechanical, thermal, and viscoelastic properties of the biocomposite. 16 Aguero et al 5 used silanization, and extrusion reactive to improve the compatibility of PLA and short flaxseed fiber, by twin-screw extrusion, to improve the mechanical properties of the injectionmolded pieces.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] For example, the incorporation of coupling agents of methylene 4,4 0 diphenyl diisocyanate and maleic anhydride in the polylactic acid/ polybutylene succinate/wood flour matrix, to improve the mechanical, thermal, and viscoelastic properties of the biocomposite. 16 Aguero et al 5 used silanization, and extrusion reactive to improve the compatibility of PLA and short flaxseed fiber, by twin-screw extrusion, to improve the mechanical properties of the injectionmolded pieces. Qian et al 17 used the Maleic Anhydride as a compatibilizer to improve the interfacial interaction of Poly (lactic acid)/Bamboo Particles biocomposites to obtain better mechanical properties.…”
Section: Introductionmentioning
confidence: 99%